(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
In recent years, the proportion of medicinal products derived from plant raw materials has been steadily increasing in modern medicine. One of the main reasons for the growing demand for plant-based drugs is their mild effect on the human body, the relatively low incidence of adverse reactions, as well as their affordability. Therefore, expanding the range of medicinal products obtained from plant raw materials is of great importance for the field of medicine [1]. In the Republic of Uzbekistan, comprehensive and systematic reforms have been implemented in recent years, aimed at the conservation of medicinal plant resources, sustainable and rational use of natural resources, establishment of specialized plantations, and development of processing technologies for medicinal plants [2]. Furthermore, proposals have been introduced by the Ministry of Agriculture of the Republic of Uzbekistan, the Ministry of Innovative Development, the State Forestry Committee, and the Agency for the Development of the Pharmaceutical Industry under the Ministry of Health to establish, starting from May 1, 2020, clusters for the cultivation, storage, primary and secondary processing of medicinal plants (hereinafter referred to as “medicinal plant clusters”), as well as to specialize regions in medicinal plant cultivation [3].